Dampak Perpajakan Penerapan Struktur Kontrak Terpisah pada Proyek Engineering, Procurement, and Construction di Indonesia - Sirait, Velix Setiawan; Suparji, Suparji; Hidayat, Yusup (UNES Law Review, 2023)
The implementation of split contract in Engineering, Procurement, and Construction (EPC) projects aims to distinguish between onshore contract or and offshore contract. Split contracts are divided into onshore contracts/domestic work contracts and offshore contracts/foreign work contracts. The application of a split contract structure in EPC projects has fundamental differences compared to the implementation of a single EPC project contract. The fundamental differences are related to taxation and exchange rate risks arising from the execution of the EPC contract itself. The implementation of a split contract structure in EPC projects in Indonesia is expected to be beneficial from the perspective of tax efficiency. The tax efficiency referred to is that onshore contractors performing work in Indonesia do not have to bear taxes on work carried out abroad. This is because the tax liability for offshore work will be borne by the employer. By taking advantage of import tax exemption rules, project owners gain tax efficiency. Split contracts (Split Contract) in EPC projects are not yet widely applied in Indonesia. Companies in Indonesia generally use a single contract structure in the implementation of EPC projects. Therefore, research is needed that discusses in detail the implementation of a split contract structure in EPC projects. This research will explore the correlation between the implementation of a split contract structure and the tax impacts on companies working on EPC projects in Indonesia. The research method used is the normative legal research method. The analysis presented in this research is based on Indonesian Tax Law, Customs and Excise Law, and other applicable legal instruments at present.